OPERAS Innovation Lab: Supporting Innovative Scholarly Outputs in Social Sciences and Humanities - Maryl, Maciej; Wnuk, Magdalena; Umerle, Tomasz (Septentrio Conference Series, 2023)
Scholars see innovative means of disseminating their work and data as a chance to improve the process of sharing ideas with different audiences, thanks to technological affordances. They understand innovation either in terms of form (novel means of communicating ideas through different media), or access (opening up outputs and making them easily accessible) (cf. Maryl and Błaszczyńska 2021, p. 34). What we consider a “scholarly text” has thus become understood as an expression that can employ different media and engage creatively with underlying data. However, engaging with novel forms of communication poses new challenges to scholars, who may lack competencies, know-how, or adequate resources to take full advantage of innovative outputs (Tasovac et al. 2018). This poster will outline the means of support provided by OPERAS Innovation Lab in establishing interdisciplinary, collaborative workflows for supporting innovative outputs in social sciences and humanities (SSH) throughout their lifecycle. The Lab provides guidelines on how to create and sustain FAIR innovative outputs in the SSH. In the current infrastructure-development project (OPERAS-PLUS) Lab’s website was created (https://lab.operas-eu.org/) and serves as an innovation observatory, collecting and storing data and studies on innovative outputs as well as current research in that field. Apart from the general introduction to the Lab, the poster will showcase three diverse case studies analysed in the ongoing project. They all aim at addressing the actual needs faced by SSH researchers who decide to use innovative forms of disseminating their output: The novel publication of project outputs: scholarly toolkit; Management of an interdisciplinary online journal; Prototyping software services for open science on the example of a recommender system for open access books based on text and data mining (Snijder 2021). A case study workflow is firstly discussed with the scholars responsible for the project to identify their needs regarding the process and the challenges they are encountering, such as issues of intellectual and technological sustainability or evaluation of non-traditional outputs. Then, in an iterative process, solutions are prototyped, involving various stakeholders, like publishers or e-infrastructures (Ell and Hughes 2013), to forge best practices and provide practical advice. This process is based on a principle of an open collaboration whereby different users will be able to engage with the process and thus the workflow itself will be open for contributions from the wider community through feedback and consultation events, such as this poster presentation.